Factor Analysis of MYB Gene Expression and Flavonoid Affecting Petal Color in Three Crabapple Cultivars - Zhang, Jie; Liu, Yingying; Bu, YuFen; Zhang, Xi; Yao, Yuncong (Frontiers in Plant Science, 2017)
Flavonoid biosynthesis has received much attention concerning the structural genes and expression of the associated transcription factors (TFs). In the present study, we examined the gene expression patterns for petals of three colors using a statistical method. Factor analysis was successfully used to examine the expression patterns most present during regulation. The first expression patterns in the white and red petals were clearly demonstrated and have revealed different mechanisms of producing the proper components, whereas that in the pink petals was more complex, requiring factor analysis to supplement the other results. Combining the results of the correlation analysis between TFs and structural genes, the effects of each TF on the main expression pattern in each cultivar were determined. Moreover, McMYB10 was implicated in the regulation of the gene expression pattern in red petals, and McMYB5 was implicated in the maintenance of the balance of the pigment components and proanthocyanin (PA) production in cooperation with McMYB4 to generate pigmentation in the pink petals.